PREVALENCE OF Aflatoxin B1 in finished commercial Broiler feed FROM west Central pakistan - N. Rashid; M. A. Bajwa; M. Rafeeq; M. A. Khan; Z. Ahmad; M. M. Tariq; A. Wadood; F. Abbas (Journal of Animal and Plant Sciences, 2012)
Aflatoxin contamination of poultry feed results in heavy economic loss and a potential risk for human being. Finished commercial broiler feed (n=96) samples collected from different broiler farms for the period June 2009 to May 2010 from south west Pakistan were analyzed for aflatoxin B1(AfB1) by using thin layer chromatography with a detection limit of 3µg/kg. Analysis revealed that 91.66% samples were positive with a range 10 to 166µg/kg and mean 47.64±2.55µg/kg. Highest level of AfB1 was found in the month of September ranged from 42 to 166µg/kg with mean of 83.25±16.11µg/kg. Categorically 82.30% samples were above the permissible limit recommenced by United States Food and Drug Administration. A significant (P<0.05) effect of season on aflatoxin production was noted. The prevalence of AfB1 may be attributed to poor harvesting technique, insect infestation, storage or environmental conditions.
Keywords: aflatoxin; broiler; poultry feed; prevalence.